The Effects of Self-Confidence, Self-Efficacy, and Metacognitive Skills on the Mathematical Problem-Solving Ability of Elementary School Teacher Education Students at STKIP Andi Matappa - Rustinah Rustinah; Vivi Rosida; Nur Asriyanti Jabir (Jurnal Studi Guru dan Pembelajaran, 2026)
Mathematical problem-solving ability is an essential competency that university students must possess to develop critical, logical, and systematic thinking skills. However, preliminary observations revealed that students of the Elementary School Teacher Education Program (PGSD) at STKIP Andi Matappa still encounter difficulties in applying mathematical concepts, selecting appropriate problem-solving strategies, and explaining mathematical concepts in their own words. This limitation is assumed to be influenced by internal factors, namely self-confidence, self-efficacy, and metacognitive skills. This study aimed to examine the partial and simultaneous effects of self-confidence, self-efficacy, and metacognitive skills on the mathematical problem-solving ability of PGSD students at STKIP Andi Matappa. The study employed a quantitative approach using an ex post facto research design. The population consisted of fifth-semester PGSD students at STKIP Andi Matappa, who also served as the research sample. Data were collected using self-confidence, self-efficacy, and metacognitive skills questionnaires, as well as a mathematical problem-solving test. The data were analyzed using descriptive statistics, classical assumption tests, significance tests, and the coefficient of determination (R²) to determine both the individual and simultaneous effects of the independent variables on students' mathematical problem-solving ability. The findings indicate that self-confidence, self-efficacy, and metacognitive skills have a significant influence on the mathematical problem-solving ability of PGSD students at STKIP Andi Matappa.